A De Novo Heterodimeric Due Ferri Protein Minimizes the Release of Reactive Intermediates in Dioxygen‐Dependent Oxidation. (14th November 2017) - Chino, Marco; Leone, Linda; Maglio, Ornella; D'Alonzo, Daniele; Pirro, Fabio; Pavone, Vincenzo; Nastri, Flavia; Lombardi, Angela
Abstract: Metalloproteins utilize O2 as an oxidant, and they often achieve a 4‐electron reduction without H2 O2 or oxygen radical release. Several proteins have been designed to catalyze one or two‐electron oxidative chemistry, but the de novo design of a protein that catalyzes the net 4‐electron reduction of O2 has not been reported yet. We report the construction of a diiron‐binding four‐helix bundle, made up of two different covalently linked α2 monomers, through click chemistry. Surprisingly, the prototype protein, DF‐C1, showed a large divergence in its reactivity from earlier DFs (DF: due ferri, two iron). DFs release the quinone imine and free H2 O2 in the oxidation of 4‐aminophenol in the presence of O2, whereas Fe III ‐DF‐C1 sequesters the quinone imine into the active site, and catalyzes inside the scaffold an oxidative coupling between oxidized and reduced 4‐aminophenol. The asymmetry of the scaffold allowed a fine‐engineering of the substrate binding pocket, that ensures selectivity.